Evaluation of the effect of polishing on flexural strength of feldspathic porcelain and its comparison with autoglazing and over glazing - Jalali H.; Aghajani F.; Shirzadi F (Tehran University of Medical Sciences, 2005)
Statement of Problem: Ceramic restorations are popular because they can provide the most natural replacement for teeth. However, the brittleness of ceramics is a primary disadvantage. There are various methods for strengthening ceramics such as metal framework, ceramic cores, and surface strengthening mechanisms through glazing, work hardening and ion exchange. Purpose: The purpose of this study was to evaluate the effect of polish on flexural strength of feldspathic porcelain and to compare it with overglaze and autoglaze. Materials and Methods: In this experimental study, one brand of feldspathic porcelain (colorlogic, Ceramco) was used and forty bars (25×6×3 mm) were prepared according to ISO 6872 and ADA No. 69. The specimens were randomly divided into four groups: overglazed, auto glazed, fine polish and coarse polish (clinic polish). Flexural strength of each specimen was determined by three point bending test (Universal Testing Machine, Zwick 1494, Germany). Collected data was analyzed by ANOVA and post-hoc test with P<0.05 as the limit of significance. Results: A significant difference was observed among the studied groups (P<0.0001). According to post-hoc test, flexural strength in overglaze and fine polish group were significantly stronger than clinic polish and autoglaze group (P<0.001). Although the mean value for overglazed group was higher than fine polish group, this was not statistically significant (P=0.9). Also no statistical difference was seen between autoglazed and coarse polish group (P=0.2). Conclusion: Based on the findings of this study, flexural strength achieved by fine polish (used in this study) can compete with overglazing the feldespathic porcelains. It also can be concluded that a final finishing procedure that involves fine polishing may be preferred to simple staining followed by self-glazing.